Gender Differentials in Working Duration Among Child Labour in Odisha, India - Narzary, Pralip Kumar (Economic Journal of Nepal, 2013)
Child labours are the victim of crushing poverty fighting for survival at an early age. Female child labours are doubly disadvantaged due to their working status and existing gender discrimination. This paper attempts to investigate into the gender differentials in working duration among child labour in Odisha by taking National Family Health Survey 2005–06 data. Although there is no apparent gender differential in terms of percentage of working, but differential in working duration is quite evident. The gender differential in duration of overall working slackens at the higher age group, whereas the differential widens in terms of engagement in household chores by age. Irrespective of socio-economic condition of the household, the gender differentials in child labour persists in Odisha. Existing policies to eliminate child labour may be gender sensitized and stringently implemented.